Combinatorial Minigenome Systems for Emerging Banyangviruses Reveal Viral Reassortment Potential and Importance of a Protruding Nucleotide in Genome “Panhandle” for Promoter Activity and Reassortment - Ren, Fuli; Zhou, Min; Deng, Fei; Wang, Hualin; Ning, Yun-Jia (Frontiers in Microbiology, 2020)
Banyangvirus is a new genus (Phenuiviridae family, Bunyavirales order) that comprises a group of emerging tick-borne viruses with severe fever with thrombocytopenia syndrome virus (SFTSV) and Heartland virus (HRTV) as virulent representatives. As segmented RNA viruses, bunyaviruses may have genome reassortment potential, increasing the concern about new life-threatening bunyavirus emergence. Using a series of combinatory minigenome reporter assays based on transfection and superinfection, we showed that replication machinery proteins of designated banyangviruses can recognize genomic untranslated regions (UTRs) of other banyangviruses and assemble heterogenous minigenomes into functional ribonucleoproteins (RNPs). Moreover, both heterogenous and heterozygous RNPs were efficiently packaged by viral glycoproteins into infectious virus-like particles, manifesting remarkable reassortment potential of banyangviruses. Meanwhile, UTR promoter strength of the three banyangvirus segments appeared to be M > L > S. Secondary structure analysis revealed a conservative non-basepairing protruding nucleotide in the terminal UTR panhandles of M and L (but not S) segments of all banyangviruses and some related phleboviruses (Phlebovirus genus). Furthermore, not only a conserved panhandle region but also the protruding nucleotide proved important for UTR function. Removal of the protruding nucleotide abated M and L UTR activities and compatibilities with heterogenous viral proteins, and introduction of a protruding nucleotide into S panhandle, conversely, enhanced UTR promoter strength and compatibility, revealing the significance of the protruding nucleotide as a new signature of the genomic panhandle structure in both UTR activity and reassortment potential. The study demonstrates not only banyangvirus reassortment potential but also the notable role of the protruding nucleotide in UTR function and reassortment, providing clues to viral evolution and replication mechanisms and perhaps benefiting disease control and prevention in the future.